Acid‐base equilibrium: The best clinical approach☆. Issue 3 (2015) - Aristizábal‐Salazar, Raúl E.; Calvo‐Torres, Felipe L.; Valencia‐Arango, Luis Alfonso; Montoya‐Cañon, Mauricio; Barbosa‐Gantiva, Oscar; Hincapié‐Baena, Vanessa
Abstract : ABSTRACT : Acid‐base balance disorders can be found in a primary or secondary form in patients with a disease process such as Diabetes Mellitus or acute renal failure, among others. The objective of this article is to explain and guide the correlationship between the clinical findings in the patient and the parameters of arterial blood gases in a simple and precise manner, in order to make the correct acid‐base balance diagnosis and adequate therapeutic interventions. A non‐systematic review of the scientific literature was conducted through a search in the PubMed, Science Direct, Scopus, and OvidSP databases. The conclusion was that base excess or deficit in arterial blood gases is a useful tool which along with the clinical history, pH, and partial pressure of CO2, provides an accurate estimate of the metabolic component of the acid‐base balance. Abstract : RESUMEN : Las alteraciones del Equilibrio Ácido‐Base se pueden presentar en pacientes de forma primaria o secundaria a un proceso patológico como la Diabetes Mellitus o la falla renal entre otros. El objetivo es explicar y orientar la correlación clínica del paciente con los parámetros de los gases arteriales de manera sencilla y precisa, para realizar un diagnóstico de las alteraciones del Equilibrio Ácido‐Base correcto, que permita efectuar intervenciones terapéuticas adecuadas y oportunas. Se realizó una revisión no sistemática de la literatura científica en la cual se consultaron las siguientes bases de datos: PubMed, ScienceDirect, Scopus y OvidSP en busca de artículos relevantes. Se concluyó que el exceso o déficit de base es una herramienta útil de los gases arteriales, que aunada a la historia clínica, el pH y la presión parcial de CO2 estima de forma muy precisa el componente metabólico del Equilibrio Ácido‐Base.